Effect of Conditioning Temperature on Pellet Quality, Diet Digestibility, and Broiler Performance - M.V. Teixeira Netto (Journal of Applied Poultry Research, 2019)
SUMMARY: Pelleting is the most common heat processing method used in the poultry feed industry and the quality of feed processing directly impacts the efficiency of the utilization of feedstuffs by broilers, and consequently, their performance. The objective of this experiment was to evaluate the influence of conditioning temperature on pellet physical quality, and on the apparent ileal digestibility coefficients of dry matter (CIADDM), crude protein (CIADCP) and starch (CIADstarch), coefficient of apparent metabolizability of dry matter (CAMDM), and the apparent metabolizable energy content (AME) of the diets. The live performance of broilers (feed intake, FI; weight gain, WG; and feed conversion ratio, FCR) was evaluated. Treatments consisted of a mash diet and pelleted/crumbled corn-soybean meal based diets submitted to different conditioning temperatures (no conditioning or conditioned at 60, 70, 80, and 90°C). Feed was steam-conditioned for 15 s at a 1.5 kgf/cm2 for all pelleted treatments. Pellet quality was determined as a function of Pellet Durability Index (PDI), percentage of fines, and pellet hardness. Conditioning temperature linearly increased (P < 0.05) PDI and pellet hardness, CIADDM, CIADCP, and CIADstarch, had quadratic effect on AME and CAMDM (P < 0.05). Broiler FI was not affected by the different conditioning temperatures, but WG and FCR presented a quadratic behavior (P < 0.05). Overall, current results suggest that the increase on conditioning temperature is an important tool to improve physical quality of pelleted diets as well as protein and starch availability. However, high conditioning temperatures may reduce broiler performance.